Evolution of the Knowledge of Free Radicals and Other Oxidants - Di Meo, Sergio; Venditti, P. (Oxidative medicine and cellular longevity, 2020)
Free radicals are chemical species (atoms, molecules, or ions) containing one or more unpaired electrons in their external orbitals and generally display a remarkable reactivity. The evidence of their existence was obtained only at the beginning of the 20th century. Chemists gradually ascertained the involvement of free radicals in organic reactions and, in the middle of the 20th century, their production in biological systems. For several decades, free radicals were thought to cause exclusively damaging effects . This idea was mainly supported by the finding that oxygen free radicals readily react with all biological macromolecules inducing their oxidative modification and loss of function. Moreover, evidence was obtained that when, in the living organism, free radicals are not neutralized by systems of biochemical defences, many pathological conditions develop. However, after some time, it became clear that the living systems not only had adapted to the coexistence with free radicals but also developed methods to turn these toxic substances to their advantage by using them in critical physiological processes. Therefore, free radicals play a dual role in living systems: they are toxic by-products of aerobic metabolism, causing oxidative damage and tissue dysfunction, and serve as molecular signals activating beneficial stress responses. This discovery also changed the way we consider antioxidants. Their use is usually regarded as helpful to counteract the damaging effects of free radicals but sometimes is harmful as it can block adaptive responses induced by low levels of radicals.